PENGEMBANGAN MEDIA EBOOK CERGAM BERBASIS KEARIFAN LOKAL BATIK TANJUNG BUMI UNTUK MENINGKATKAN KARAKTER SISWA - Kusni Kusni; Nasution Nasution; Agus Suprijono; Hendratno Hendratno (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2021)
oABSTRACTl This study aimslto produce learning media to improve the social character of elementary school students. Character values based on local wisdom from the Tanjung Bumi Batik motif were developed in the pictorial stories ebook media. This study uses a04D development model. (define, design,kdevelop, andddisseminate). The subjects ofhthis study were fourth grade students A as the experimental group and grade IV B students as the control group at SDN Tengket 2, Arosbaya District, Bangkalan Regency. The results of the study found that: 1.) the meaning and value of Batik Tanjung Bumi is in accordance with the implementation of ‘Penguatan Pendidikan Karakter’ (PPK) contained in Permendikbud number 20 of 2018, namely honest, hard work, peace-loving, disciplined, independent, and religious characters. 2.) pictorial stories ebook media is declared very feasible to use based on the results of material validation of 91.43% and media validation of 100%. 3.) the practicality of the comic book media was obtained by observation with a score of 92% for individual trials, 87.5% for small group trials, and 88% for field tests with very good categories. 4.) the results of the test of the effectiveness of the pictorial stories ebook media were obtained from the pretest and posttest in the experimental group and control group with a P-value (0.000) <0.05 and the difference in the N-gain score is 0.27, which indicates that the N-gain score of the experimental group is higher than the N-gain score of the control group. Thus, it can be concluded that the use of the developed pictorial stories ebook media can improve the social character of the fourth grade students of SDN Tengket 2 effectively.Keywords: pictorial stories ebook media, social character education, local wisdom, Batik Tanjung Bumi